2012
DOI: 10.1186/1756-3305-5-174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Galba truncatula, Lymnaea neotropica and L. schirazensis from Cajamarca, Peru and their potential role in transmission of human and animal fascioliasis

Abstract: BackgroundHuman and animal fascioliasis is emerging in many world regions, among which Andean countries constitute the largest regional hot spot and Peru the country presenting more human endemic areas. A survey was undertaken on the lymnaeid snails inhabiting the hyperendemic area of Cajamarca, where human prevalences are the highest known among the areas presenting a "valley transmission pattern", to establish which species are present, genetically characterise their populations by comparison with other huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 60 publications
(140 reference statements)
3
50
1
1
Order By: Relevance
“…In agreement with Bargues et al (2012), we believe that without the molecular analyses, the specimens studied in this work would be erroneously identified as G. viatrix or G. cubensis. In Mendoza province G. neotropica was first identified as G. viatrix based on the morphology of the shell and the internal organs, and then correctly identified by using COI sequences (Standley et al 2013).…”
Section: Galba Neotropicasupporting
confidence: 78%
See 2 more Smart Citations
“…In agreement with Bargues et al (2012), we believe that without the molecular analyses, the specimens studied in this work would be erroneously identified as G. viatrix or G. cubensis. In Mendoza province G. neotropica was first identified as G. viatrix based on the morphology of the shell and the internal organs, and then correctly identified by using COI sequences (Standley et al 2013).…”
Section: Galba Neotropicasupporting
confidence: 78%
“…1). In Peru it was found in Lima (type locality) and Cajamarca (Bargues et al 2007(Bargues et al , 2012; in Venezuela it was found in Carabobo and Falcón (Bargues et al 2011) and in Argentina it was found in Mendoza, northern Patagonia (Mera y Sierra et al 2009;Standley et al 2013) and Buenos Aires, Central region (Sanabria et al 2012). Identities of all these records were achieved by molecular markers.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fasciola gigantica is transmitted by lymnaeids of larger size of the Radix group (Bargues and Mas-Coma, 2005). The presence of lymnaeid vectors defines not only the distribution of fascioliasis, but may also explain the distribution of human infection within a country, as has been recently observed in different countries (Artigas et al 2011;Bargues et al 2011b, c), and within an endemic area, as well as its seasonality or permanent transmission (Bargues et al 2012). In southern Asia, G. truncatula is restricted to the highlands in countries such as Afghanistan and Pakistan (Kendall, 1954(Kendall, , 1965 and its absence as well as the lack of appropriate Galba/Fossaria lymnaeid species for the development of F. hepatica in India and eastward up to South-east Asia is well known (Mas-Coma et al 2009a).…”
Section: Discussionmentioning
confidence: 79%
“…It can be assumed that liver fluke is European origin, with the snail Limnaea truncatula as the original intermediate host. Some authors suggest the potential of this wild host in the fascioliasis transmission (Bargues et al, , 2012Khoubbane et al, 2004;Mas-Coma et al, 2009). The liver fluke Fasciola hepatica plays an important role as a parasite of wild and farm animals.…”
Section: Introductionmentioning
confidence: 99%